Plasticity of morphogenesis and features of reproduction of Colobanthus quitensis and Deschampsia antarctica plants in Antarctic region - Kravets, O.A.; Taran, N. Yu.; Storozhenko, V. O. (Ukrainian Antarctic Journal, 2012)
The anatomic structure of reproductive organs of two endemic species of plants of Antarctic region (Deschampsia antarctica and Colobanthus quitensis) were investigated. Structural and functional features of organization of reproductive organs of both species were revealed. This features contribute to adaptation of plants to low temperature action. Some of them are ephemerality and intensity of reproduction, cleistogamy, special anatomy appliances of perianth and germ, three-cell type of pollen grains.